A strategy of KIT-6-carrier modification towards enhancement of desulfurization properties of mesoporous Zn-based sorbents for H2S removal from hot coal gas. (1st April 2023) - Duan, Xinwei; Wu, Mengmeng; Feng, Yu; Li, Yang; Mi, Jie
Highlights: Ti/W doped KIT-6 for sorbents was synthesized via one-pot synthesis method. Doping of Ti and W show different effects on porosity of carriers. The dispersion of ZnO can be improved by using doped KIT-6 as carrier. The modification of carriers results in better H2 S removal property. Sorbents with Ti doped carriers exhibits higher sulfidation/regeneration stability. Abstract: Modification of KIT-6 by Ti/W doping (with one-pot synthesis method) was proposed for improving desulfurization performance of ZnO-KIT-6 sorbent. The characterization results indicate that the dopant atoms are present in the form of Ti 4+ and W 6+, the ordered mesoporous structure of KIT-6 can be retained at Me/Si doping ratios of 1/50–1/20. The presence of [TiO4 ] 4− units in Ti-doped carriers demonstrates that a part of Ti atoms incorporates into the silica framework. Furthermore, moderate Ti doping causes more porous KIT-6 but W doping results in the decline in the specific surface area. Metal doping of Ti/W both show the effects of pore expansion as well as improvement of ZnO-dispersion, favorable for the sulfidation reaction. Generally, the desulfurization properties of sorbents are greatly enhanced by carrier modification. The highest breakthrough sulfur capacity of sorbents containing Ti or W doped KIT-6 are approximate (7.07 and 7.14 g S/100 g sorbent for Ti and W doping, respectively). However, W modification results in greater decrease in orderness of carriers. Additionally, sorbent with Ti-doped carriers has more stable H2 S-uptake capacity during five successive sulfidation/regeneration cycles, showing great potential for industrial applications.